KERAGAMAN BIOLOGIS IKAN KERAPU SUNU (Plectropomus leopardus) DI KEPULAUAN SPERMONDE SULAWESI SELATAN - Ernaningsih, Ernaningsih; Budimawan, Budimawan; Nessa, Natsir; Sudirman, Sudirman (Hasanuddin University, 2015)
Fisheries management requires reliable estimation and can be made as a consequence of the alternatives strategyexploitation, it requires knowledge about the biological condition of the fish stocks at a certain time, one of them is agrouper (Plectropomus leopardus).The aims of this study is to analyze the biological diversity includes the averagetotal length, size structure and weight-length relationship of groupers (Plectropomus leopardus) in SpermondeIslands. The results are expected to provide information on sustainable resource management in SpermondeArchipelago.The study was conducted from July 2013- February 2014 in three locations of Spermondearchipelago,namely Sarappo Island, LumulumuIsland and LangkaiIsland using primary data. Research methodssuch as measurement of total length and weight of the grouper Sunufish from the catch of fishermen and traders ineach collection area. The average of the total length, the size structure and weight length relationships wereanalyzed descriptively,The analysis results of the average total length of the grouper (P. leopardus) caught inSarappo Island, Lumulumu Island and Langkai Island respectively 29.84 ± 8.6 cm (N = 624), 31.93 ± 8.03 cm ( N =291), 34.64 ± 7.41 cm (N = 214) where the nearer them to the mainland,the smaller averagetotal length is. The sizedistribution of grouper sunu (P. leopardus) in the Sarappo island and Lumulumu island are most of the small sizewhich is 22.5 cm by 35.63% and 22.68%, and on the Langkai island the most caught fishes size are 37.5 cm by 31,77%. Weight-length relationship on the three islands are minor allometric,Keywords: total length, structure size, weight length relationship, grouper Spermonde Archipelago